Impelementasi Sak Emkm Dalam Penyusunan Laporan Keuangan Menggunakan Accurate Accounting Pada UMKM Hakuna Matata - Pratiwi, Nabila; Rahmi, Fitria; Dahar , Reni (CV. ITTC INDONESIA, 2024)
The number of small, micro and medium enterprises (MSMEs) in Indonesia has increased significantly, but only a few MSMEs have implemented an accounting system in their financial records. Hakuna Matata MSMEs still carry out accounting records manually through recording expenses and receipts so that the owner does not know the exact amount of inventory and profit or loss earned. Manual recording can cause recording errors and the risk of losing data. The method used by the author in this research is descriptive qualitative with the type of case study. The data obtained is processed and then implemented into accurate software. From this research it can be concluded that the application of accurate software in Hakuna Matata MSMEs will ensure the preparation of financial reports more quickly and accurately, MSMEs can also find out the company's profit or loss. Computerized sales and purchase transactions also make it easy to find out inventory stock. The application of financial statements in accordance with SAK EMKM presents financial statements consisting of three components, namely the Statement of financial position, Income Statement and notes to financial statements prepared based on financial reports from accurate software.